Evidence for Carbonate System Mediated Shape Shift in an Intertidal Predatory Gastropod - Mayk, Dennis; Peck, Lloyd S.; Harper, Elizabeth M. (Frontiers in Marine Science, 2022)
Phenotypic plasticity represents an important first-line organism response to newly introduced or changing environmental constraints. Knowledge about structural responses to environmental stressors could thus be an essential measure to predict species and ecosystem responses to a world in change. In this study, we combined morphometric analyses with environmental modelling to identify direct shape responses of the predatory gastropod Nucella lapillus to large-scale variability in sea surface temperature and the carbonate system. Our models suggest that the state of the carbonate system and, more specifically, the substrate inhibitor ratio ([HCO3−][H+]−1) (SIR) has a dominant effect on the shell shape of this intertidal muricid. Populations in regions with a lower SIR tend to form narrower shells with a higher spire to body whorl ratio, whereas populations in areas with a higher SIR form wider shells with a much lower spire to body whorl ratio. These results indicate that a widespread phenotypic response of N. lapillus to continuing ocean acidification can be expected, potentially altering the phenotypic response pattern to predator or wave exposure regimes with profound implications for North Atlantic rocky shore communities.